2021
DOI: 10.1088/1755-1315/739/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient content of compost produced by earthworm in the utilization of livestock waste using vermicomposting method

Abstract: The development of livestock should be focusing on increasing productivity and maximizing profit and the environmental issue that happens around it. The produced waste can be managed by minimalizing the waste generated by turning it into something valuable or reutilizing it. One way to do it is by utilizing the waste as organic fertilizer (vermicompost). The vermicomposting process resulted in two products that are useful for agriculture; there are earthworm and vermicompost itself. Using the generated waste a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Abdimas perlu dilakukan tahun berikutnya untuk memastikan bahwa petani melanjutkan penggunaan pupuk organic untuk tanaman hortikultura buah seperti Alpukat dan Manggis. Banyak bahan untuk pengolahan pupuk organik yang dapat direkomendasikan seperti, Bio-urine merupakan pupuk organik cair yang berasal dari pengolahan limbah ternak (Vebriyanti et al, 2022), memanfaatkan limbah ternak sebagai pupuk organik (kascing) (Iresha et al, 2021). Direkomendasikan juga pengolahan Eceng gondok yang ditambahkan dengan limbah tongkol jagung hasil penelitian (Fitrihidajati, et al, 2021).…”
Section: Tindak Lanjut Dan Rekomendasiunclassified
“…Abdimas perlu dilakukan tahun berikutnya untuk memastikan bahwa petani melanjutkan penggunaan pupuk organic untuk tanaman hortikultura buah seperti Alpukat dan Manggis. Banyak bahan untuk pengolahan pupuk organik yang dapat direkomendasikan seperti, Bio-urine merupakan pupuk organik cair yang berasal dari pengolahan limbah ternak (Vebriyanti et al, 2022), memanfaatkan limbah ternak sebagai pupuk organik (kascing) (Iresha et al, 2021). Direkomendasikan juga pengolahan Eceng gondok yang ditambahkan dengan limbah tongkol jagung hasil penelitian (Fitrihidajati, et al, 2021).…”
Section: Tindak Lanjut Dan Rekomendasiunclassified
“…Another technology is utilization of earthworm that often mention as vermicomposting. Previous studies found that vermicomposting can reduce organic waste but take long time with moderate until less reduce of the organic waste [3,4]. The latest trend of reducing the organic waste is the usage of insect larvae as bioconversion.…”
Section: Introductionmentioning
confidence: 99%